SIMULASI DENSE WAVELENGTH DIVISION MULTIPLEXING (DWDM) DENGAN MENGGUNAKAN APLIKASI CISCO PACKET TRACER - Deva Adelya Prestanty; Aditya Dwi Raja Kamansastra; Alamsyah Alamsyah; Didik Aribowo (Pusat Riset dan Inovasi Nasional, 2023)
The development of Dense Wavelength Division Multiplexing (DWDM) technology in optical networks driven by the need for very large transmission capacities has resulted in rapid changes in the provision of large bandwidth capacities in networks. This canal transport system in the wavelength domain provides high flexibility for network operators in meeting current and future needs.